Pemertahanan Kelas Hegemonik dalam Pertunjukan Ngadu Domba Garut - Febryani, Irma (Postgraduate Program of Institut Seni Budaya Indonesia Bandung, 2019)
Sheepfight (Ngadu Domba) as one of the performances highly favored by the people has many changes especially from the performance issues. The sheepfight is not an activity only for fun. It is more as the means for raising the living standard of the people especially of the sheepfight farmer. The research applies qualitative method. The data are obtained through observation, interview, literature study, and documentation. Antonio Gramsci’s hegemony theory is applied to analyze the issues in this study. The research question in this study is how HPDKI organization maintain its power as hegemonic class in Garut sheepfight performance. The regulation of HPDKI stabilize its position as hegemonic class. HPDKI has its own strength by consistently approaching and negotiating with the people during certain time.Keywords: Ngadu Domba Garut, Hegemonic, Performance